EDUKASI PENGELOLAAN SAMPAH DI DESA BATANG BABASAL KECAMATAN TOTIKUM KABUPATEN BANGGAI KEPULAUAN SULAWESI TENGAH - Sandy Novryanto Sakati; Maria Kanan; Ika Anatasya Padaela; Melda Gienardy (Universitas Nusa Bangsa, 2026)
Waste management issues in Batang Babasal Village, Totikum District, Banggai Islands Regency, remain a challenge for the community due to low knowledge and awareness regarding sorting and managing household waste. This situation has the potential to cause environmental pollution, health problems, and degrade the quality of the village environment. This community service activity aims to improve community knowledge and attitudes regarding proper waste management. The activity methods include outreach, education, mentoring, and evaluation through lectures and interactive discussions. This activity involved 75 respondents who were given pre- and posttests to measure changes in their knowledge and attitudes before and after the activity. The pretest results showed that 43 respondents had poor knowledge (57%). After the educational activity, 65 respondents (87%) had good knowledge and demonstrated positive changes in attitudes toward waste management. Thus, the waste management education activity has been proven to improve community knowledge and attitudes in Batang Babasal Village. It is hoped that this improvement will encourage changes in community behavior towards independent waste management, thereby creating a clean, healthy, and sustainable environment.